Experimental and numerical analysis of deflection of posttensioned lightweight concrete slabs. Issue 22 (17th November 2019) - Vakhshouri, Behnam
ABSTRACT: This study utilizes the RAM Concept program to evaluate the previously conducted experimental results of deflection of three series of unbonded posttensioned lightweight concrete slabs with different mixture design and span length. Effect of provision in different codes of practice to estimate the deflection of posttensioned slabs is compared. Long-term deflection of slabs is analyzed and the effect of span length and mechanical properties of concrete are evaluated. There are considerable differences to estimate the short-term and long-term deflections by different design codes. The span length shows an inevitable effect on accuracy of the estimated deflection by different codes of practice.